Intense Arm Rehabilitation Therapy Improves the Modified Rankin Scale Score: Association Between Gains in Impairment and Function. (6th April 2021) - Cramer, Steven C.; Le, Vu; Saver, Jeffrey L.; Dodakian, Lucy; See, Jill; Augsburger, Renee; McKenzie, Alison; Zhou, Robert J.; Chiu, Nina L.; Heckhausen, Jutta; Cassidy, Jessica M.; Scacchi, Walt; et al.
Abstract : Objective: To evaluate the effect of intensive rehabilitation on the modified Rankin Scale (mRS), a measure of activities limitation commonly used in acute stroke studies, and to define the specific changes in body structure/function (motor impairment) most related to mRS gains. Methods: Patients were enrolled >90 days poststroke. Each was evaluated before and 30 days after a 6-week course of daily rehabilitation targeting the arm. Activity gains, measured using the mRS, were examined and compared to body structure/function gains, measured using the Fugl-Meyer (FM) motor scale. Additional analyses examined whether activity gains were more strongly related to specific body structure/function gains. Results: At baseline (160 ± 48 days poststroke), patients (n = 77) had median mRS score of 3 (interquartile range, 2–3), decreasing to 2 [2–3] 30 days posttherapy ( p < 0.0001). Similarly, the proportion of patients with mRS score ⩽2 increased from 46.8% at baseline to 66.2% at 30 days posttherapy ( p = 0.015). These findings were accounted for by the mRS score decreasing in 24 (31.2%) patients. Patients with a treatment-related mRS score improvement, compared to those without, had similar overall motor gains (change in total FM score, p = 0.63). In exploratory analysis, improvement in several specific motor impairments, such as finger flexion and wrist circumduction, was significantly associated with higher likelihood of mRS decrease. Conclusions: Intensive arm motor therapy is associated with improved mRS in a substantial fraction (31.2%) of patients. Exploratory analysis suggests specific motor impairments that might underlie this finding and may be optimal targets for rehabilitation therapies that aim to reduce activities limitations. Clinical Trial: Clinicaltrials.gov identifier: NCT02360488. Classification of Evidence: This study provides Class III evidence that for patients >90 days poststroke with persistent arm motor deficits, intensive arm motor therapy improved mRS in a substantial fraction (31.2%) of patients.